IMF Research Bulletin, June 2016. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 2016)
In the June 2016 issue of IMF Research Bulletin, Eugenio Cerutti interviews Lars E.O. Svensson. Lars, a professor at the Stockholm School of Economics, was a Visiting Scholar at the IMF. In the interview, he discusses monetary policy, financial stability, and life at the IMF. The Bulletin also features a listing of recent Working Papers, Staff Discussion Notes, and key IMF publications. The table of contents from the latest issue of IMF Economic Review is also included.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet